ANALISIS PRODUKSI KOMODITAS PANGAN DAN PENGARUHNYA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO PERTANIAN DI KABUPATEN MAGELANG - Adhy Wicaksana, Andreas Richo; Setiadi, Agus; Mukson (JURNAL LITBANG PROVINSI JAWA TENGAH, 2022)
Magelang Regency is a food commodity-producing Regency which makes Magelang Regency one of the fulfillments of food needs for the surrounding area. This study aims to determine the basic and non-basic sectors, analyze the development trend of food commodity production (rice, large chili, sugarcane and beef) in Magelang Regency, and analyze the effect of food commodity production on the gross regional domestic product (GDP) of the agricultural sector in Magelang Regency. The data used are time series data from 2003 to 2021. The methods used in this study are Partial Adjustment Model (PAM), Classical Assumption Test, Least Square method and location quotient analysis. The results showed that the variables of rice, chili, sugarcane and beef production had no significant effect on the Gross Regional Domestic Product (GRDP) of the Agricultural Sector of Magelang Regency both in the long and short term. The Gross Regional Domestic Product (GRDP) of the Agricultural Sector of Magelang Regency in the previous period had a significant effect on the Gross Regional Domestic Product of the Agricultural Sector of Magelang Regency. Trend analysis in the production of rice, chili and beef experienced an increase but the production of sugarcane experienced a negative trend. Location quotient analysis shows that large rice and chili are included in the basic sector while sugarcane and beef are not included in the basic sector.